Musika a documentary on Philippine music (Tuklas sining series, 1989)
Traces the fusion of East and West in Philippine music. Highlights music as the expression of the Filipino soul in the indigenous sali-dum-ay; hispanized religious (masses, hymns) and secular forms (kundiman, habanera, danza, polka); the Americanized popular music (blues, jazz and the rock and roll); and contemporary music (serious music, pinoy pop and protest songs).